Obox1 deficiency impairs fertility in female mice - Li Wu; Jiacheng Shen; Zhenzhen Hou; Yinli Zhang; Yan Bi; Ran Zhang; Heping Bai; Wen Ye; Kang Chen; Jiang Zhu; Chenxiang Xi; Yiliang Xu; et al. (Fundamental Research)
OBOX1 is a maternal factor involved in oogenesis and follicle development, yet its specific role remains unclear. Here, we demonstrated that Obox1 knockout female mice exhibit subfertility, characterized by reduced litter size and impaired ovulation. These oocytes show minimal disruption in early embryonic development post-fertilization. However, Obox1 deficiency leads to decreased levels of gonadotropins and female sex hormones, especially the luteinizing hormone (LH). Exogenous human chorionic gonadotropin (hCG) administration during superovulation failed to rescue the ovulation defect. Post-ovulation, the ovulation-related genes and serum progesterone levels were significantly reduced in Obox1-deficienct ovaries, accompanied by dysregulated steroidogenesis-related gene expression. Transcriptomic profiling of Obox1 deficient metaphase II (MII) oocytes revealed downregulation of genes involved in mitochondrial energy metabolism and biosynthesis, and upregulation of genes associated with cell transport, transcription, RNA processing, translation. Further investigation revealed that follistatin gene expression was upregulated in both MII oocytes and ovaries of Obox1 deficient mice, along with increased expression of Gdf9, Bmp15, Foxl2, and NOTCH signaling components. These findings suggest that Obox1 is essential for maintaining hormonal balance and ovulatory function through regulating oocyte-granulosa cell interactions and steroid hormone synthesis.